TRACING THE TRAILS OF PALEMBANG'S ULAMA NETWORK THROUGH PODCASTS: INNOVATION IN LOCAL HISTORY LEARNING IN THE DIGITAL ERA: Menelusuri Jejak Jaringan Ulama Palembang Melalui Podcast: Inovasi Pembelajaran Sejarah Lokal Di Era Digital - Nadhifa Khairunnisa; Dede Khaerunisa; Syarifuddin Khaerunisa; Tyas Fernanda (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
Local history plays a crucial role in strengthening national identity and cultural awareness among the younger generation. However, in the digital era, challenges arise from students' lack of interest in historical material, which they consider boring. This study aims to explore how podcasts can serve as an innovative tool in local history learning, focusing on the network of ulama (Islamic scholars) in Palembang as the object of study. Using a literature study method, this study collected and analyzed data from various literature sources discussing the role of ulama in the development of Islamic education in the archipelago and the potential of podcasts in education. The results show that podcasts can present local history narratives in a more engaging and interactive manner. The use of an audio format allows for more engaging information delivery, facilitates listener engagement, and disseminates diverse perspectives on the ulama's intellectual heritage. Therefore, this study recommends integrating podcasts into the educational curriculum to enhance students' understanding of local history. It is hoped that this innovation can strengthen cultural identity and foster a love of history among the digital generation, especially in Palembang's society, which is rich in tradition and history.